Mobile edge computing and application in traffic offloading - Jianmin ZHANG; Weiliang XIE; Fengyi YANG; Zhouyun WU; Liang XIE (Dianxin kexue)
Mobile edge computing（MEC）makes it possible to deploy and provide service locally,which is close to the users,by enabling the IT and cloud computation capacity at the radio access network (RAN).Thus,MEC can improve the quality of experience (QoE) by reducing the latency,and decrease the network operation cost through reducing backhaul capacity requirement.Meanwhile,based on the network context information (location,network traffic load,radio information,etc) exposure to applications and services,MEC can further improve the QoE of user and provide the platform to third-party partners for application and service innovation.Besides the introduction of MEC,the detailed MEC platform was presented.Furthermore,the traffic offloading solution based on MEC was proposed and compared with the solution of local IP access and selected IP traffic offload (LIPA/SIPTO).In addition,the problems and challenges of the MEC were also discussed in detail.